This Body of Death : A Novel - George, Elizabeth 1949- (New York : HarperCollinsPublishers, 2010)
After a woman is found dead in an isolated cemetery, Inspector Thomas Lynley and his former partner, Barbara Havers, find that the roots of the crime trace to a long-ago act of violence that has poisoned subsequent generations.
Keywords: Great Britain -- Metropolitan Police Office -- Fiction; Lynley, Thomas(Fictitious character)-Fiction -- Fiction; Women detectives -- Fiction -- England; London (England) -- Fiction; Fiction